Real Power Loss Reduction by Amplified Water Cycle Algorithm - Lenin, Kanagasabai (Yayasan Ahmar Cendekia Indonesia, 2020)
In this paper Amplified Water Cycle Algorithm (AWCA) has been used to solve the optimal reactive power problem. Water cycle algorithm (WCA) is a methodology which inspired by the hydrological cycle which happen in nature. In this work water cycle algorithm hybridized with Gravitational Search Algorithm, Chaos theory. In the projected Amplified Water Cycle Algorithm (AWCA) - with reference to the fitness value, population is first alienated into three groups: streams, rivers and sea. Through this hybridization exploration and exploitation is effectively improved. Positions of particles are initially modernized according to gravitational search. Chaos theory is then defined and integrated in water cycle algorithm to modernize the population which will augment explore capability and population diversity. Projected Amplified Water Cycle Algorithm (AWCA) has been tested in standard IEEE 14, 30, 57, 300 bus test system and simulation results show the projected algorithm reduced the real power loss extensively.